2016
DOI: 10.1002/nau.22989
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Urinary Sphincter: Report of the 2015 Consensus Conference

Abstract: These guidelines undoubtedly constitute a reference document, which will help urologists to carefully select patients and apply the most adapted management to implantation, follow-up and trouble-shooting of the AMS800™.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
72
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 178 publications
(251 reference statements)
0
72
0
2
Order By: Relevance
“…Published literature supports AMS 800 device as a highly durable, effective (up to 90%) and safe surgical option in male SUI with high patient satisfaction rate (44-48). Recent consensus among high volume implanters reported that AMS 800 implantation remains a highly-specialized surgery with surgical challenges and that careful patient selection and appropriate surgical care remain paramount in optimal surgical outcomes (49). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Published literature supports AMS 800 device as a highly durable, effective (up to 90%) and safe surgical option in male SUI with high patient satisfaction rate (44-48). Recent consensus among high volume implanters reported that AMS 800 implantation remains a highly-specialized surgery with surgical challenges and that careful patient selection and appropriate surgical care remain paramount in optimal surgical outcomes (49). …”
Section: Methodsmentioning
confidence: 99%
“…A recent multicentre study found that penoscrotal single-cuff implantation resulted in significantly higher short-term explantation rates compared to perineal single-cuff AUS (19.2% vs. 8.6%; P=0.019) and that postoperative infection rate was significantly higher after double-cuff compared to single-cuff implantation (6% vs. 13.9%; P=0.019) (50). Revision and explantation rates due to mechanical failure, urethral atrophy, infection, and cuff erosion vary considerably among published studies (46-49,51). The reported reoperation rate for AUS is around a third of the cases, with about 50% of these cases caused by mechanical complications and 50% by non-mechanical complications (46-49,51).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A report of a Consensus Conference (5), based on the most recent data available in literature as well as expert opinions, was recently published outlining a wide array of challenges. The Consensus highlights the need to inform patients about expected rates of mechanical failure, erosion and infection which would result in a re-operation rates ranging from 14.8% to 44.8%.…”
mentioning
confidence: 99%